“Pasangan Minimal” Fonem Dasar Pembelajaran Materi Fonologi Bahasa Indonesia - Ary Setyadi (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2018)
Evidence as well as the goal of writing articles related to the statement: that the existence of "minimal pair" phonemes are supposed to be the basis/early learning Indonesian phonology is based on the following reasons: a. functional phoneme "minimal pair", b. certainty of speech and phoneme symbols, c. certainty of type and number of phonemes, d. phoneme as the cause of difference/contrast of meaning (words), and e. other forms of antonym formation (i).Starting from the effort of proof and the goal, finally it can be said: that such a study is an important study, because from several literature sources there is a phoneme "minimal pair" only discussed in a brief and simple manner. That is only limited to capacity as a means of proofing phonemes to phonemic traits. In other words, it turns out that the existing problems have never been discussed in depth and specifically.The method applied is based on three strategic stages, namely: 1. provision of data, 2. classification and analysis of data, and 3. preparation of reports/writing. The data is obtained from written sources, so that the provision of data is secondary. The application of theory is based on the linguistic theory of phonology and the semantic field. The application of the phonology field is related to the effort to put words in the phoneme "minimum pair", while the semantic field is related to the different meanings (words) of the paired words.